Pengembangan Kostum Carnival dengan Inspirasi Arsitektur Candi Prambanan - Ariyana Damayanti; Yurista Nirmalasari (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Clothing is not only a primary clothing worn as body protection in everyday life, but has developed into clothing as a work of art. One of them is clothing designed for a big event with certain friends such as carnival or carnival clothing. Carnival costumes are designed to display creativity, joy, and cultural diversity. The design is often inspired by local cultural elements, such as mythology, flora, fauna, or traditional symbols. Carnival costumes are made of various materials, such as cloth, feathers, sequins, glitter, and others. This clothing is made to create a striking, beautiful, and eye-catching appearance. The author considers the historical background, mythology, architecture, and local culture related to temples in Indonesia, can produce carnival costumes that are not only visually appealing, but also rich in meaning and cultural values. The general objective of this study is to determine how the Development of Carnival Costumes with Prambanan Temple Architectural Inspiration. The method used is using the Research and Development (R&D) approach through the ADDIE development model. Each stage of ADDIE (Analysis, Design, Development, Implementation, and Evaluation) is used to systematically direct the costume creation process, from identifying needs to evaluating the final results. Determining factors such as measurements, errors, and weight of the clothing. Ergonomic design will allow carnival participants to move freely and comfortably.